Impact of commercialization in rice seed production on crop productivity and household income - Panta, H. K. (Journal of the Institute of Agriculture and Animal Science, 2018)
To assess the impact of commercial rice seed production on rice productivity and household income, a survey study was conducted in Gorkha, Lamjung and Tanahun districts of Nepal covering eight seed production groups. Analyses include probit regression and cost and returns from seed production. Results of the probit model showed that agricultural training, increase in household income, average age of household head, use of modern rice cultivars, household size, and involvement of women in agricultural decision making have significant positive effect on adoption of the modern rice seed production technology. Similarly, significant difference between non-adopters and adaptors was observed in relation to seed productivity. Study showed that yield of improved seed technologies are higher by 2 ton/ha than the traditional rice varieties and net income is around NRs 43,500 per hectare. Study also showed that the improved rice seed technologies, amount of seed applied, area planted, and fertilizer applied are highly significant variables affecting rice productivity. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page:11-18